Corporate internet reporting within malaysian economic sectors - Turmin, Siti Zaidah; Abdul Hamid, Fatima; Mohamad Ghazali, Nazli Anum (Universita Putra Malaysia, 2016)
Corporate Internet Reporting (CIR) is the communication process between corporation and stakeholders via the Internet medium. The Malaysian economy in 2015 was ranked 14th in the world and 5th in countries with a population exceeding 20 million, is one of the most competitive countries in the world. The use of CIR by Malaysian corporations in diverse economic sectors is considered as a precondition for success. This study looks into the elements of CIR practice by 310 publicly listed Malaysian corporations across various economic sectors. In addition, the influence drivers for CIR practiced by the corporations has also been examined. In measuring the level of CIR in use, this study has developed a CIR index with 41 attributes. Data was gathered for a period of three months and analysed using descriptive statistics and multiple regression method. The results revealed that the level of CIR practiced by Malaysian corporations varies across economic sectors, with certain sectors dominating the level of practice in specific CIR categories. Size, profitability and economic sector are significant in determining the CIR practice of corporations. Finally, the study contributes to the knowledge pertaining to CIR in Malaysia as it examines the actual level of CIR practiced by corporations in various economic sectors.